Bladder outlet obstruction in women - Shirish Yande; Maya Joshi (Wolters Kluwer Medknow Publications, 2011)
Bladder outlet obstruction in females remains a poorly understood condition and is much rarer as compared to males. More difficult is the objective diagnosis of this condition. There is no general agreement on the Urodynamic parameters to define the condition with certainty. A number of conditions are involved particularly in urinary retention in females are not completely understood. Besides, external sphincter dysfunction and post surgical retentions add another group of conditions which are distinct from retentions seen in the males. This article takes a review of various aetiological factors of Bladder outlet obstruction in women. An attempt is made to standardise the Urodynamic parameters for use in females, based on our data and experimentation on the models of the bladder and urethra. This article also takes a review of uncommon conditions such as Fowler's syndrome which often complicate evaluation of this condition.